Wireless network access selection scheme for heterogeneous multimedia traffic. Issue 4 (1st December 2013) - Mehbodniya, Abolfazl; Kaleem, Faisal; Yen, Kang K.; Adachi, Fumiyuki
Abstract : Global connectivity, at anyplace and anytime, to provide high‐speed, high‐quality and reliable communication channels, is now becoming a reality. The credit mainly goes to the recent technological advances in wireless communications, which consist of a wide range of technologies and applications to fulfil the particular needs of end‐users in different deployment scenarios (Bluetooth, Wi‐Fi, WiMAX and third generation/fourth generation cellular systems). In such a heterogeneous wireless environment, one of the key ingredients to provide efficient ubiquitous computing is the design of intelligent handoff algorithms, which select the optimal target network. This study presents a novel approach for the design and implementation of a multi‐criteria vertical handoff decision algorithm for heterogeneous wireless networks to achieve seamless mobility while maximising end‐users' satisfaction. Two important modules are designed; the first module estimates the necessity of handoffs and the second module selects the best network as the target of handoff. Several parallel fuzzy logic controllers with reduced rule sets are used, in combination with a fuzzy ranking algorithm, to implement these modules. Simulation results are provided and compared with a benchmark for different evaluation metrics.